Analysis of Factors Affecting Taxpayer Compliance Paying Hotel Tax, Restaurant Tax and Entertainment Tax in Medan City - Mahyuliza Mahyuliza; M. Fitri Rahmadana; Eko Wahyu Nugrahadi (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
Regional tax revenue in Medan City as a source of financing has increased quite significantly, therefore local taxes remain the prima donna for financing regional expenditures in Medan City. For the Government of Medan City, although the fiscal capacity that comes from local revenue is still limited, local taxes still play an important role in increasing tax revenue in Medan City. Based on Law Number 28 Year 2011, hotel, restaurant and entertainment tax collection implements a self-assessment system so that taxpayer awareness is a very determining factor for taxpayer compliance in carrying out tax obligations and rights. This study aims 1) to analyze the effect of tax knowledge, service quality, tax audit on taxpayer awareness of paying hotel taxes, restaurant taxes and entertainment taxes in Medan City; 2) to analyze the effect of tax knowledge, service quality, tax inspection and taxpayer awareness on taxpayer compliance of paying hotel taxes, restaurant taxes and entertainment taxes in Medan City. The research method used is quantitative research methods. There are two sources of data used, namely primary data and secondary data obtained from the Medan City Revenue Service. The data collection method used was a questionnaire. Sampling was done by accidental sampling. The analytical tool used is descriptive analysis and path diagram analysis. The results of hypothesis testing carried out by path analysis show that 1) tax knowledge, service quality and tax audits have a positive effect on taxpayer awareness of paying hotel taxes, restaurant taxes and entertainment taxes in Medan City; 2) service quality and tax audits have no effect on taxpayer compliance paying hotel, restaurant and entertainment taxes in the city of Medan, while tax knowledge tax inspection and taxpayer awareness have a positive effect on taxpayer compliance paying hotel taxes, restaurant taxes and entertainment taxes in Medan city; because the amount of hotel tax revenue, restaurant tax and entertainment provide a high contribution to local taxes in Medan City.